Rebellion against Reason? A Study of Expressive Choice and Strikes - Christa N. Brunnschweiler; Colin Jennings; Ian A. MacKenzie (ETH Zurich, CER-ETH - Center of Economic Research, 2012)
In this paper we challenge the conventional view that strikes are caused by asymmetric information regarding firm profitability such that union members are uninformed. Instead, we build an expressive model of strikes where the perception of unfairness provides the expressive benefit of voting for a strike. The model predicts that larger union size increases both wage offers and the incidence of strikes. Furthermore, while asymmetric information is still important in causing strikes, we find that it is the employer who is not fully informed about the level of emotionality within the union, thereby contributing to strike incidence. An empirical test using UK data provides support for the predictions. In particular, union size has a positive effect on the incidence of strikes and other industrial actions even when asymmetric information regarding profitability is controlled for.
Keywords: D03; D72; J52; 330; strikes; expressive voting; Gewerkschaftsmitgliedschaft; Arbeitskampf; Motivation; Asymmetrische Information; Arbeitskräfte; Schätzung; Großbritannien